1985
DOI: 10.1172/jci112196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen peroxide exposure on normal human erythrocyte deformability, morphology, surface characteristics, and spectrin-hemoglobin cross-linking.

Abstract: To further define the conditions for forming spectrin-hemoglobin cross-linking in human erythrocyte membranes and to examine its possible effects on membrane function, we incubated normal human erythrocytes for up to 3 h in concentrations of H202, varying from 45 to 180 ;.M, in an azide phosphate buffer, pH 7.4. The chemical changes observed indicated that methemoglobin formation occurred early and at a low concentration (45 MM). Morphologic changes characterized by increased echinocyte formation occurred in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
168
1
4

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(203 citation statements)
references
References 23 publications
19
168
1
4
Order By: Relevance
“…In fact, the correct energy balance of H 2 O 2 -treated erythrocytes was obtained only by taking into consideration concentrations of dephosphorylated metabolites, either those detected in erythrocyte extracts or those determined in the suspending medium. For instance, according to this calculation, the value of S NT + IMP + intra-and extra-cellular oxypurines and nucleosides was < 2030 mmol´L 21 and 1990 mmol´L 21 in control and 4 mm H 2 O 2 -treated erythrocytes, respectively. As reported in Fig.…”
Section: R E S U L T Smentioning
confidence: 87%
“…In fact, the correct energy balance of H 2 O 2 -treated erythrocytes was obtained only by taking into consideration concentrations of dephosphorylated metabolites, either those detected in erythrocyte extracts or those determined in the suspending medium. For instance, according to this calculation, the value of S NT + IMP + intra-and extra-cellular oxypurines and nucleosides was < 2030 mmol´L 21 and 1990 mmol´L 21 in control and 4 mm H 2 O 2 -treated erythrocytes, respectively. As reported in Fig.…”
Section: R E S U L T Smentioning
confidence: 87%
“…Because halohydrins are undetectable at these levels, it seems likely that modification of membrane and cytoskeletal proteins is responsible for haemolysis. It is interesting that studies with different oxidative systems have also found that protein modification, rather than lipid peroxidation, is associated with haemolysis [32,39,40]. There were two major differences in the effects of HOBr and HOCl on membrane proteins : (1) with HOBr there was selective loss of band 3 that was almost complete at the lowest dose of oxidant (4 nmol per 10( cells) and (2) irreversible protein cross-linking of most of the proteins occurred more readily with HOBr.…”
Section: Discussionmentioning
confidence: 99%
“…FOR cause oxidant-induced changes in the structure and function of erythrocyte membranes. Major changes reported by different researchers are lipid peroxidation, membrane protein-crosslinkings and oxidation of heme proteins resulting in their crosslinkings to skeletal proteins, i.e spectrin, actin, cytoplasmic component of band 3 (47)(48)(49)(50). Free oxygen radicals induced changes result in severe deteoriation of membrane structure and function causing increases in osmotic fragility ratios, accelerated cell aging and premature cell death ultimately.…”
Section: Discussionmentioning
confidence: 99%